PENGENDALIAN INTERN KAS DALAM USAHA MENINGKATKAN EFISIENSI PENGGUNAAN DANA - Erni Salijah (Jurnal Mirai Management, 2020)
The purpose of this study was to predict the level of bankruptcy in PT. HM Sampoerna, Tbk. and PT. Gudang Garam, Tbk. The type of data used is qualitative data and quantitative data. The data source used secondary data. The analytical method used is the Altman Z-Score method. The results of this study indicate that the results of the analysis of the Altman Z-Score on PT. HM Sampoerna, Tbk.and PT. Gudang Garam, Tbk. warehouse. In 2018-2019 shows good result, where both of these companies have Z-Score above 2,6. At PT. HM Sampoerna, Tbk. in 2018 the Z-Score was 12,0816 > 2,6. And in 2019 the Z-Score was 10,5251 > 2,6. While in PT. Gudang Garam ,Tbk. in 2018 the Z-Score was 7,3407 > 2,6 and in 2018 the Z-Score was 7,5251 > 2,6. So in the calculation of the Altman Z-Score model Altman Z-Score model that can predict bankruptcy Z-Score > 2,6 which in indicate by the company in a safe condition or non bankrupt. Keywords: Altman Z-score, bankruptcy prediction